PARAMETER HAK ASASI MANUSIA (HAM) NASIONAL DALAM PEMBUATAN PERATURAN DAERAH - Suroto S.H., M.H. (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2014)
In the good governance framework, law enforcement even become one of principles that should be done when a government wants to be categorized as clean and respectable government. Legal formation through transparent and participative legislative process were also characterized the democratic government. The establishment and enforcement of human rights law has strategic value as it relates to the government legitimation. Government gained power through the people sovereignty-basedelections mechanism further elaborated in legal authority and law which underlying the authorization. Law plays an important role as rules that limit the power and direct the use of force to prevent arbitrary and human rights violations. At this point is where the establishment and enforcement of law relating to human rights. Problems which faced by the local government in the establishment and enforcement of human rights law is raised by the differences perception of the human rights law concept itself, as results of different backgrounds, interests and understanding. It resulted on the difficulty of human rights lawenforcement.In addition, legal certainty is one of the important factors required to createconducive stability in the local development.